MEREDUPNYA GERAKAN MAHASISWA PASCA PEMILIHAN PRESIDEN 2014 - Ruslan Ismail Mage (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Ngurah Rai, 2020)
The fading of the Student Movement after the 2014 Presidential Election. This writing uses a library research method. The problems in this paper are divided into three parts. First, why does the student movement tend to weaken (dim) in the face of Joko Widodo's regime? Second, what is the cause of the dimness of the student movement? Third, how to revive the enthusiasm of students as agents of change in this country? The finding was that the student movement showed unhealthy signs by losing their enthusiasm. The climax was after the 2014 presidential election, which put Joko Widodo as the people's choice of president, it was felt that the student movement from day to day was getting fainter and lost the spirit of their struggle. Even if there is student action it is already polarized, so the echo is very weak.